Формирование испытательных импульсов тока сложной формы - Петков, Александр Александрович (НТУ "ХПИ", 2004)
This paper considers the parameters selection of the elements of the discharge circuit of the current pulses generator by formation complex form pulses. The parities allowing to make such selection are resulted.
Keywords: импульс тока; электромагнитное воздействие; операторный метод